TIME COURSE OF COGNITIVE FUNCTIONING DURING THE FIRST YEAR AFTER ISCHEMIC NON-LACUNAR STROKES IN PATIENTS WITH ATRIAL FIBRILLATION - Delva, M.Yu.; Zayets, V.V.; Chekalina, N.I.; Delva, I.I. (World of Medicine and Biology, 2024)
Atrial fibrillation is a significant risk factor for the development of post-stroke cognitive impairment. We studied the regularities of the changes in cognition during the first year after ischemic non-lacunar stroke in patients with atrial fibrillation. We recruited patients with persistent (paroxysmal) and permanent forms of atrial fibrillation, and patients with regular sinus rhythm who experienced an ischemic non-lacunar stroke within the last 6 months. Cognitive testing (Mini-Mental State Examination, Montreal Cognitive Assessment, Clock Drawing Test, and Frontal Assessment Battery) was performed after inclusion in the study and then again at 6, 9, and 12 months following the stroke. In the first year after ischemic non-lacunar strokes, people with permanent (paroxysmal) and persistent atrial fibrillation had statistically significant detrimental modifications in global cognition (as evaluated by Mini-Mental State Examination and Montreal Cognitive Assessment) when compared to patients with regular sinus rhythm. In patients with both types of atrial fibrillation, visuospatial and executive functions exhibit worsening during the first year after ischemic non-lacunar strokes (significant decline in the “Visuospatial-executive” domain of Montreal Cognitive Assessment, in clock drawing test, and frontal assessment battery).